Analisis Sistem Pemantauan Pemisah Sampah Logam dan Non Logam berbasis Internet of Things - Muchamad Malik; Sumpena Sumpena (Jurnal Engine: Energi, Manufaktur, dan Material, 2023)
Waste has become a serious problem, especially in big cities, not only in Indonesia but also around the world. Waste production continues to increase along with population growth, and changes in consumption patterns and people's lifestyles have increased the amount of waste, the type, and the diversity of waste characteristics. Waste bins are infrastructure available in every city park that makes it easier for park visitors to dispose of waste. make it easier for park visitors to dispose of waste. In some places, There are no bins based on the basic material of the waste, namely metal bins and non-metal bins that can be monitored in real-time. So a smart trash can is made that can sort metal or non-metal waste that can be monitored in real-time with the Internet of Things. The hardware used is Metal Proximity Sensor, Infrared Sensor, Servo Motor, Ultrasonic Sensor, MQ135 Gas Sensor, and ESP32 Microcontroller. The capacity in the trash can be monitored through the Blynk application, which will provide notification when the trash can is full. Based on the test results of the volume reading of the trash can, the success of the sensor to open and close is 99.26%. To sort non-metal waste and metal waste using proximity sensors with the results of testing the reading of waste objects obtained success in non-metal waste by 95% and metal waste by 100%.